Acute exposure to ultraviolet radiation targets proteins involved in collagen fibrillogenesis - Platt, Christopher I.; Stewart-McGuinness, Callum; Eckersley, Alexander; Wilkins, Loren; Sherratt, Michael J. (Frontiers in Physiology, 2024)
Exposure to chronic, low-dose UV irradiation (UVR) can lead to premature ageing of the skin. Understanding which proteins are affected by acute UVR and photo-dynamically produced reactive oxygen species (ROS) could help to inform strategies to delay photoageing. Conventional biochemical analyses can be used to characterize UVR/ROS-induced damage on a protein-by-protein basis and we have previously shown using SDS-PAGE that collagen I and plasma fibronectin are respectively resistant and susceptible to physiological doses of UVR. However, methods to screen complex proteomes for affected proteins have been lacking. The aim of this study was to use a sensitive mass spectrometry technique (peptide location fingerprinting: PLF) which can identify structure associated differences following trypsin digestion to characterize the impact of UVR exposure on purified collagen I and tissue fibronectin and to identify UVR-susceptible proteins in an ECM-enriched proteome. Using LC/MS-MS and PLF we show that purified mature type-I collagen is resistant to UVR, whereas purified tissue fibronectin is susceptible. UV irradiation of a human dermal fibroblastdeposited ECM-enriched proteome in vitro, followed by LC/MS-MS and PLF analysis revealed two protein cluster groups of UV susceptible proteins involved in (i) matrix collagen fibril assembly and (ii) protein translation and motor activity. Furthermore, PLF highlighted UV susceptible domains within targeted matrix proteins, suggesting that UV damage of matrix proteins is localized. In conclusion, this study demonstrates that PLF can be used to identify protein targets of UVR and that collagen accessory proteins may be key targets in UVR exposed tissues.